Emerging trends in nano-sensors: A new frontier in food safety and quality assurance - Farhang Hameed Awlqadr; Ammar B. Altemimi; Syamand Ahmed Qadir; Tablo Azad Hama Salih; Zina T. Alkanan; Qausar Hamed AlKaisy; Othman Abdulrahman Mohammed; Mohammad Ali Hesarinejad (Heliyon)
The rapid evolution of nanotechnology has catalyzed significant advancements in the design and application of nano-sensors, particularly within the food industry, where ensuring safety and quality is of paramount concern. This review explores the multifaceted role of nano-sensors constructed from diverse nanomaterials in detecting foodborne pathogens and toxins, offering a comprehensive analysis of their operational principles, sensitivity, and specificity. Nano-sensors leverage unique physical and chemical properties at the nanoscale to enhance the detection of microbial contamination, actively contributing to food safety protocols. With applications ranging from real-time monitoring of pathogenic bacteria, such as Escherichia coli and Salmonella, to assessing environmental factors affecting food quality, these innovative devices demonstrate unparalleled advantages over conventional detection methods. Recent research illustrates the integration of nano-sensors with biosensing techniques, enabling multiplex analysis and rapid detection. Furthermore, the review addresses current challenges in the commercialization and regulatory landscape of nano-sensor technology, emphasizing the need for ongoing research to optimize their performance and facilitate widespread adoption in food safety systems. Overall, the incorporation of nano-sensors represents a transformative approach to safeguarding public health by proactively managing food safety risks and enhancing the efficiency of food quality assurance processes.